From Digital Exclusion to Adaptive Inclusion: Policy Innovations to Bridge Social Divides in Next-generation Regional Planning in Indonesia - Ningrum, Sinta (KnE Social Sciences, 2025)
This study examines the impact of Indonesia’s digital transformation policies on regional social equity, with a focus on disparities between the Western and Eastern regions. Utilizing a comparative methodology with quantitative and qualitative data from government assessments, including the electronic-based government system (SPBE) and Indonesia Digital Society Index (IMDI) from 2022 to 2024, the research identifies spatial, institutional, and policy disparities. The analysis revealed persistent regional digital divides, with Western Indonesia consistently outperforming Eastern Indonesia in both digital readiness and citizen capacity. A positive correlation between IMDI and SPBE scores indicates that societal digital readiness and e-government maturity evolve in tandem. However, these advancements have not equally benefited all regions. The observed digital gaps reflect deeper structural inequalities, necessitating policy innovation for inclusive development. The findings underscore the importance of adaptive, context-specific interventions that align community empowerment with bureaucratic modernization. This study recommends asymmetric, capacity-building programs, performance-based digital equity grants, and the establishment of Regional Digital Transformation Zones (RDTZs) to bridge the digital equity gap and promote inclusive digital transformation in Indonesia.